GNSS Aided Long-Range 3D Displacement Sensing for High-Rise Structures with Two Non-Overlapping Cameras - Dongsheng Zhang; Zhenyang Yu; Yan Xu; Li Ding; Hu Ding; Qifeng Yu; Zhilong Su (Remote Sensing, 2022)
Image-based displacement measurement techniques are widely used for sensing the deformation of structures, and plays an increasing role in structural health monitoring owing to its benefit of non-contacting. In this study, a non-overlapping dual camera measurement model with the aid of global navigation satellite system (GNSS) is proposed to sense the three-dimensional (3D) displacements of high-rise structures. Each component of the dual camera system can measure a pair of displacement components of a target point in a 3D space, and its pose relative to the target can be obtained by combining a built-in inclinometer and a GNSS system. To eliminate the coupling of lateral and vertical displacements caused by the perspective projection, a homography-based transformation is introduced to correct the inclined image planes. In contrast to the stereo vision-based displacement measurement techniques, the proposed method does not require the overlapping of the field of views and the calibration of the vision geometry. Both simulation and experiment demonstrate the feasibility and correctness of the proposed method, heralding that it has a potential capacity in the field of remote health monitoring for high-rise buildings.